Case Report: Clinical manifestations of uncommon monogenic disorders: revisiting activated phosphoinositide 3-kinase delta syndrome 2 - Shamriz, Oded; Mandola, Amarilla; Simon, Amos J.; Lev, Atar; Attal, Pierre; Nadler, Chen; Barel, Ortal; Khavkin, Yulia; Eisenberg, Rachel; Somech, Raz; Toker, Ori (Frontiers in Pediatrics, 2025)
AimPediatricians are trained to identify recurrent or unusual infections in children, prompting evaluation for inborn errors of immunity (IEI). Some monogenic IEI, however, may present atypically. This study describes our experience with children diagnosed with activated phosphoinositide 3-kinase delta syndrome (APDS2) including unusual presentations.MethodsA retrospective review was conducted on two children diagnosed with APDS2 at Shaare Zedek and Sheba Tel-Hashomer Medical Centers in Israel. Both patients underwent immune assessments, genetic testing, and treatment between 2019 and 2024.ResultsTwo patients, a 17-year-old female (P1) and a 7-year-old male (P2), were diagnosed with APDS2 after presenting with recurrent juvenile parotitis (P1) and severe lymphadenopathy (P2). Immunologic evaluation revealed hypogammaglobulinemia and combined immune deficiency. Genetic testing identified PIK3R1 variants (c.1425 + 1G > T in P1 and c.1425 + 1G > C in P2). Both received intravenous immunoglobulins and prophylactic antibiotics. P2 was treated with rapamycin, leading to resolution of lymphadenopathy.ConclusionThis report highlights the clinical presentation of APDS2, a rare monogenic IEI in children, including the atypical manifestation of RJP and the common feature of lymphadenopathy. Pediatricians should stay vigilant for red flags of IEI during clinical evaluations, as early diagnosis and multidisciplinary care are crucial for effective management.